Recent Advancements in the Cobalt Oxides, Manganese Oxides, and Their Composite As an Electrode Material for Supercapacitor: A Review - Uke, Santosh J.; Akhare, Vijay P.; Bambole, Devidas R.; Bodade, Anjali B.; Chaudhari, Gajanan N. (Frontiers in Materials, 2017)
Recently, our modern society demands the portable electronic devices such as mobile phones, laptops, smart watches, etc. Such devices demand light weight, flexible, and low-cost energy storage systems. Among different energy storage systems, supercapacitor has been considered as one of the most potential energy storage systems. This has several significant merits such as high power density, light weight, eco-friendly, etc. The electrode material is the important part of the supercapacitor. Recent studies have shown that there are many new advancement in electrode materials for supercapacitors. In this review, we focused on the recent advancements in the cobalt oxides, manganese oxides, and their composites as an electrode material for supercapacitor.